2009
DOI: 10.1242/dev.038141
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of a notochord cis-regulatory module by Brachyury and FoxA in the ascidianCiona intestinalis

Abstract: The notochord is a defining feature of the chordate body plan. Experiments in ascidian, frog and mouse embryos have shown that co-expression of Brachyury and FoxA class transcription factors is required for notochord development. However, studies on the cisregulatory sequences mediating the synergistic effects of these transcription factors are complicated by the limited knowledge of notochord genes and cis-regulatory modules (CRMs) that are directly targeted by both. We have identified an easily testable mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 49 publications
(60 reference statements)
1
55
0
Order By: Relevance
“…We then proceeded with the ChIP assays of the remaining notochord CRMs, along with adequate controls (Figure 8C and unpublished data). The results demonstrated that in addition to the Ci-tune minimal CRM [41], which served as one of our positive controls, the Ci-Noto1 , Ci-Noto4 , Ci-Noto5 , Ci-Noto9 , Ci-FCol1 , Ci-lamc1 , and Ci-thbs3 CRMs are also bound in vivo by Ci-Bra. On the other hand, the minimal Ci-ACL notochord CRM, which we have shown to be devoid of Ci-Bra binding sites, was not specifically recognized, similar to the negative control used for these experiments, 18S rRNA gene.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We then proceeded with the ChIP assays of the remaining notochord CRMs, along with adequate controls (Figure 8C and unpublished data). The results demonstrated that in addition to the Ci-tune minimal CRM [41], which served as one of our positive controls, the Ci-Noto1 , Ci-Noto4 , Ci-Noto5 , Ci-Noto9 , Ci-FCol1 , Ci-lamc1 , and Ci-thbs3 CRMs are also bound in vivo by Ci-Bra. On the other hand, the minimal Ci-ACL notochord CRM, which we have shown to be devoid of Ci-Bra binding sites, was not specifically recognized, similar to the negative control used for these experiments, 18S rRNA gene.…”
Section: Resultsmentioning
confidence: 94%
“…The minimal 83-bp Ci-Noto5 notochord CRM contains two Ci-Bra binding sites at its extremities and a centrally located putative Fox binding site (Figure 3H) with a TRTTTAY core. This sequence was examined because it is shared with the functional Ci-FoxA-a site that is required to activate the Ci-tune notochord CRM synergistically with Ci-Bra [41]. Interestingly, none of the individual mutations of either Ci-Bra or Ci-Fox binding sites had any detectable effect on the Ci-Noto5 CRM notochord activity (Figure 3I–3L); however, the combined mutation of both Ci-Bra binding sites completely abolished staining in notochord cells, leaving the activity in mesenchyme cells intact (Figure 3M).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the two NOCE subregions which show activity in the NNC direct expression of the full pattern albeit at reduced levels. Synergism between different transcription factor binding sites is generally observed in enhancer regions [53] and has been described for various other notochord enhancers [26], [27], [29], [54]. Since the deletion of E1 from NOCE has a more severe effect than the mutation of OBS (compare Fig 5 C d–f with 6 B a–c), and deletion of E3 affects NNC expression levels much more than mutation of the FOXA2 site (compare Fig 5 C y–za with Fig 6 B d–f ), it is highly likely that additional binding sites in the enhancer subregions E1 and E3 are required for the synergistic activity of the three enhancer subregions.…”
Section: Discussionmentioning
confidence: 74%
“…The same antibody was then affinity-purified (see Methods) and used for ChIP assays with primers specifically designed to amplify a 134-bp fragment of the Ci-tune notochord CRM. The Ci-tune notochord CRM is part of a Ciona genomic region that contains two Ci-Bra binding sites, which we have previously shown to be bound by Ci-Bra via electrophoretic mobility shift assays (Passamaneck et al 2009). Thus, the Ci-tune notochord CRM provided us with a reliable positive control.…”
Section: Resultsmentioning
confidence: 99%